EXPERIENCE OF REPORT ABOUT WASTE MANAGEMENT IN A HEALTH SERVICE - Saidelles, Ana Paula Fleig; Fassina, Ismael; Kirchner, Rosane Maria; Benetti, Joana (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611706663 Environmental problems caused by men are due to the inadequate use of the environment. Themain objective of this study is to report the authors experience. State on the program of solidwaste management in health services. This work was developed as part of an extension projectduring the second semester 2010. We carried out technical visits to the health unit, observationsand seminars on waste management and on the use of personal protective equipment. Somepreventive procedures to minimize the contamination risk were detected: not accumulate wastebags in improper places, to buy and use appropriate bags with infecting risk symbol on it,adequate use of personal (PPE) and collective (CPE) protective equipment; the preparation of aseminar to demonstrate in an objective and transparent way all these information, to encourageprevention programs in the health unit on hygiene; a safe route for waste transport with anaccessible entrance to the unit. Thereby, the change in the behavior with responsibility and environmental consciousness by the health area professionals may be turned in securealternatives for waste management.